PENGARUH KOMPETENSI GURU TERHADAP KINERJA GURU DAN PRESTASI BELAJAR SISWA DI KOTA MAKASSAR - Mukhtar, Afiah; MD, Luqman (Idaarah: Jurnal Manajemen Pendidikan, 2020)
This research is to study the competencies of teachers and student achievement. Data sources used in this study are primary and secondary data, with PNS teacher participants in the Makassar City Education and Culture Office, as for the sample of 183 teacher respondents. Analysis of the data used in this study is Structural Equation Modeling (SEM). Based on the research results obtained positive and significant competence on the performance of high school teachers in Makassar City, while the evaluation of competencies on student achievement has positive and not significant results on the learning achievement of high school students in Makassar City. Intervening variable test results obtained positive and significant assessment competence on student achievement in high school in Makassar through teacher performance, direct competency complaints against student learning achievement when teacher performance is significant on student learning achievement.